Management and cost accounting - Drury, Colin (Workingham, Berkshire, England : Van Nostrand Reinhold, 1985)
This book consists of 24 chapters divided into six parts. Part 1 consists of two chapters and provides an introduction to management and cost accounting. Part 2 consists of six chapters and focuses on cost accounting with the emphasis on allocating manufacturing costs to products to separate costs between cost of goods sold and the closing stock valuation. Part 3 consists of six chapters, and considers the notion of relevant cost and the information which should be presented to help managers to make good decisions. Part 4 consists of five chapters, and emphasizes the process for integrating the decisions into a meaningful, coordinated package via the budgeting process. Part 5 consists of three chapters, and is entitled The Application of Quantitative Methods to Management Accounting. The final part- Divisional Performance Evaluation, consists of two chapters which deal with the problems of measuring the performance of divisional managers.
Includes bibliographical references and index.
ne 13/07/2018
Loans
Keywords: Managerial accounting; Cost accounting